Los programas de formación ocupacional: una alternativa al término de la educación obligatoria - Molina Martín, Susana; Hernández García, Jesús; Rodríguez Menéndez, Mª del Carmen (Revista Complutense de Educación, 2007)
This paper analyzes the knowledge of pupils finishing the compulsory education about the program of professional qualification. We present some results and conclusions from a study carried out in the Principality of Asturias, with 2,260 pupils, who are in the 4th year of Secondary Compulsory Education, about their academic and professional expectations for the future. The results obtained allow us to conclude that pupils haven’t got enough information about these programs, regardless of where they live. So we believe that this situation would be able to change if both school centres and local agents together develop a proposal of vocational counselling.